2010
DOI: 10.1038/bmt.2010.84
|View full text |Cite
|
Sign up to set email alerts
|

Priming with r-metHuSCF and filgrastim or chemotherapy and filgrastim in patients with malignant lymphomas: a randomized phase II pilot study of mobilization and engraftment

Abstract: SCF has been shown to synergize with G-CSF to mobilize CD34 þ PBPCs. In this study we report results from this combination after a phase II trial of 32 patients with malignant lymphoma randomized to receive recombinant methionyl human SCF (ancestim, r-metHuSCF) in combination with recombinant methionyl human G-CSF (filgrastim, r-metHuG-CSF) (experimental arm A) or routine chemotherapy plus filgrastim (conventional arm B). The primary objective was to evaluate the side effects and toxicity during priming and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…We also selected two cytokines: hLIF which maintains cells in an undifferentiated state and hSCF which plays a role in the formation of blood and germ cells. hSCF is manufactured by Amgen (under the trade name STEMGEN ® ) for use in combination with NEUPOGEN ® for certain cancer patients undergoing transplantation [33,34]. Proteins involved in the formation of large protein complexes were also selected, such as UAF1, which is part of the deubiquitinating enzyme heterodimeric complex USP1-UAF1 [35]; The Cyclin Dependent Kinase 7 (CDK7), a subunit of the transcription/DNA repair factor TFIIH [36], is both an effector kinase which phosphorylates both RNA Polymerase II and other transcription factors and a Cdk Activating Kinase (CAK) for essential CDKs [37]; VPS26A, which is a subunit of the core 'Retromer' complex that mediates endosomal protein sorting and trafficking [38]; and Munc18a and Munc18c which regulate SNARE-complexes that mediate vesicle fusion [39].…”
Section: Target Proteins Selected For the Benchmarkmentioning
confidence: 99%
“…We also selected two cytokines: hLIF which maintains cells in an undifferentiated state and hSCF which plays a role in the formation of blood and germ cells. hSCF is manufactured by Amgen (under the trade name STEMGEN ® ) for use in combination with NEUPOGEN ® for certain cancer patients undergoing transplantation [33,34]. Proteins involved in the formation of large protein complexes were also selected, such as UAF1, which is part of the deubiquitinating enzyme heterodimeric complex USP1-UAF1 [35]; The Cyclin Dependent Kinase 7 (CDK7), a subunit of the transcription/DNA repair factor TFIIH [36], is both an effector kinase which phosphorylates both RNA Polymerase II and other transcription factors and a Cdk Activating Kinase (CAK) for essential CDKs [37]; VPS26A, which is a subunit of the core 'Retromer' complex that mediates endosomal protein sorting and trafficking [38]; and Munc18a and Munc18c which regulate SNARE-complexes that mediate vesicle fusion [39].…”
Section: Target Proteins Selected For the Benchmarkmentioning
confidence: 99%
“…In a retrospective analysis of 840 patients with MM or non-Hodgkin's lymphoma, 129 patients (15%) were identified as poor mobilisers and divided into three categories based on CD34 + levels in PB before leukapheresis: 'borderline' poor mobilisers (11)(12)(13)(14)(15)(16)(17)(18)(19)/μL at maximum stimulation), 'relative' poor mobilisers (6-10/μL) and 'absolute' poor mobilisers ( o5/μL). 8 Diagnosis, sex, age, body weight and previous irradiation made no significant difference in HSC mobilisation capacity.…”
Section: Algorithms To Define Poor Mobilisersmentioning
confidence: 99%
“…8 If two autografts are needed for a specific treatment strategy, even more patients fail to reach their individual collection goal. Newer approaches aiming to optimise mobilisation procedures include off-label use of pegylated G-CSF, [9][10][11][12] erythropoietin, 13 SCF 14,15 and plerixafor. [16][17][18] Nevertheless, it is necessary to optimise the current mobilisation approaches and to identify upfront the patients at risk of mobilisation failure.…”
Section: Introductionmentioning
confidence: 99%
“…1996–Oct. 1997 MM CY + G-CSF RD; CY + SCF + G-CSF RD The SCF group showed significant higher CD34 + cells yield ( P = 0.007)* Johnsen et al [ 39 ] Phase 2 RCT, open-label, multicenter NA Malignant lymphoma CY + G-CSF SD; SCF + G-CSF SD The CY plus G-CSF group showed higher number of CD34 + cells collected and higher rate of reaching optimal target on first leukapheresis ( P = 0.00018)* Stiff et al [ 60 ] RCT, multicenter NA NHL or HL G-CSF SD; SCF + G-CSF SD SCF group showed an increase in the median total CD34 + cells collected ( P = 0.05) Addition of other cytokines Hart et al [ 36 ] RCT, single center May 2004–Jan 2006 MM IEV + G-CSF RD; IEV + G-CSF RD + EPO No significant differences in the number of CD34 + cells collected ( P = 0.57) Lonial et al [ 45 ] RCT, single center NA Lymphoma or MM Chemotherapy + G-CSF SD; Chemotherapy + G-CSF RD + GM-CSF RD No significant differences in the number of CD34 + cells collected Zhu et al [ 65 ] RCT, single center 2002–2005 NHL or AML Chemotherapy + G-CSF RD; Chemotherapy + G-CSF RD + IL-11 No significant differences in the number of total CD34 + cells collected Zhu et al [ 67 ] RCT, multicenter NA NHL CE + G-CSF RD; CE + G-CSF RD + TPO The TPO group ...…”
Section: Resultsmentioning
confidence: 99%
“…GM-CSF showed no advantage in mobilization efficacy, but is associated with increased toxicity and later engrafment than G-CSF. Addition of SCF improved the mobilization efficacy of CY plus G-CSF RD in patients with MM, but SCF plus G-CSF is not superior to CY plus G-CSF [ 27 , 34 , 39 , 60 ]. Addition of TPO to mobilizing chemotherapy plus G-CSF significantly increased the number of CD34 + cells collected and the rare of achieving optimal target in patients with NHL, but addition of other cytokines including EPO, GM-CSF and IL-11 did not show significant improvement [ 36 , 45 , 65 , 67 ].…”
Section: Resultsmentioning
confidence: 99%